2017
DOI: 10.1007/s11605-017-3459-1
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Evaluation of a Clinical Pathway for Pancreaticoduodenectomy Procedures: a Prospective Cohort Study

Abstract: Introduction Medical and nursing protocols in perioperative care for pancreaticoduodenectomy are mainly mono-disciplinary, limiting their integration and transparency in a continuous health care system. The aims of this study were to evaluate adherence to a multidisciplinary clinical pathway for all pancreaticoduodenectomy patients during their entire hospital stay and to determine if the use of this clinical pathway is associated with beneficial effects on clinical end points. Materials and Methods A prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
0
11
0
1
Order By: Relevance
“…The characteristics of the 19 included articles, which comprised 7 cohort studies (8, 2328) and 12 case-control studies (7, 2939), are shown in Table 1, which totally contains 3387 patients. Thirteen studies (8, 23, 26, 2834, 3739) included patients undergoing PD, one study (35) included patients undergoing distal pancreatectomy (DP), one study (25) included patients undergoing proximal pancreatic resection, one study (36) included patients undergoing laparoscopic pancreatoduodenectomy (LDP), and three studies (7, 24, 27) included patients undergoing two forms of pancreatectomy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The characteristics of the 19 included articles, which comprised 7 cohort studies (8, 2328) and 12 case-control studies (7, 2939), are shown in Table 1, which totally contains 3387 patients. Thirteen studies (8, 23, 26, 2834, 3739) included patients undergoing PD, one study (35) included patients undergoing distal pancreatectomy (DP), one study (25) included patients undergoing proximal pancreatic resection, one study (36) included patients undergoing laparoscopic pancreatoduodenectomy (LDP), and three studies (7, 24, 27) included patients undergoing two forms of pancreatectomy.…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen studies (7, 8, 2325, 2832, 3439) reported mortality as the primary outcome (Figure 5). The OR for mortality was 0.96 (95% CI: 0.59 to 1.55).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CPs have shown favorable perioperative results for a number of operations in gastrointestinal surgery 10. Kennedy et al (2012), Walters et al (2012) and Van der Kolk et al (2017) evaluated CPs for pancreaticoduodenectomy 1113. All showed a reduction in length of stay and Kennedy et al additionally reported a non-significant decrease of overall complication rates.…”
Section: Introductionmentioning
confidence: 99%